The significance of the absolute place in the novel of the oriental manuscript of the Algerian novelist Ouassini LAREDJ - NOUADRIA, Karima (Journal of Human Sciences, 2020)
The ’’waciny’’ novel entered into special space, including material fraught with realism and living some of which suggest of generalization - in the word of Elkhamsa Allawi - leading to immensity and infinity which are surprising and create the exception and waiting which considers the sea and desert all its belongings in a novel of ’’eastern manuscript’’ one of its strongest manifestation as a spatial space intersecting in its infinity and the nature of events in time at the text level. Before that we present first a summary of the novel.